Human Resource Management Information System and Organisational Performance a Case Study of Uganda Red Cross Society, Mukono - Puot Deng Nyadoor (Uganda Christian University, 2024)
The study investigated the impact of the Human Resource Management Information System (HRMIS) on organizational performance at the Uganda Red Cross Society (URCS). The research was guided by three primary objectives: (1) to examine the role of HRMIS in improving organizational performance, (2) to determine the impact of HRMIS on customer service provision at URCS, and (3) to assess how the implementation of HRMIS has affected personnel administration at the organization. The study employed a quantitative research design with a sample size of 30 respondents, comprising management and non-management staff from the Human Resource Department (HRD) at the URCS head office and regional offices. Additionally, 30 customers were randomly selected and interviewed, with two respondents from each region. Data was collected using structured questionnaires and interviews, while a simple random sampling technique ensured that all respondents had an equal chance of selection. The findings, analyzed using Pearson rank correlation and descriptive statistics, revealed that HRMIS has a positive and statistically significant effect on organizational performance. Specifically, HRMIS contributed to improvements in personnel administration, as measured through performance measurement, performance appraisal, job analysis, recruitment, and selection applications. The second objective showed that HRMIS significantly impacted customer service, particularly through communication applications. The study concluded that regular evaluations of the HRMIS, conducted either quarterly or monthly, are essential for identifying areas requiring enhancements. Future research was proposed to explore additional aspects of HRMIS in other sectors. These findings align with previous empirical studies, further underscoring the critical role of HRMIS in enhancing both internal administrative functions and external service delivery at URCS. Keywords: Human Resource Management Information System, Organization Performance, Customer Satisfaction, Effectiveness of the Human Resource Management Information System.
Undergraduate